Comparison of Two PCRs for Detection of Mycobacterium ulcerans - Guimaraes-Peres, A. (American Society for Microbiology, 1999)
Two nested PCRs for the detection of Mycobacterium ulcerans were compared by using a collection of 65 clinical specimens. The first method amplifies the gene coding for 16S rRNA, and the second method amplifies a repetitive DNA sequence. The sensitivities of bacterioscopy, culture, 16S rRNA gene PCR, and repetitive-sequence PCR were 29, 34, 80, and 85%, respectively. Compared to the 16S rRNA gene PCR, the repetitive-sequence PCR was faster, easier to perform, and less expensive.